Extracellular Proteolysis and Angiogenesis - Pepper, Michael S. (Thrombosis and Haemostasis, 2001)
Extracellular proteolysis is an absolute requirement for new blood vessel formation, a process known as angiogenesis. This review will examine the role of the matrix metalloproteinase and plasminogen activator/plasmin systems during angiogenesis. Extracellular proteolysis has also been implicated in the generation of molecules with angioregulatory activity. These include, but are not limited to, angiostatin and endostatin. However, despite an abundance of data on their bioactivity, the molecular mechanisms by which these molecules achieve their effects are unknown. Anti-proteolysis, particularly in the context of angiogenesis, has become a key target in therapeutic strategies aimed at inhibiting tumor growth and other diseases associated with neovascularization.
Keywords: Matrix; metalloproteinase; plasminogen; angiostatin; endostatin